Front Matter - Alice G. Brand (Editor) (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
Editor's Message Many of us come out of formal and advanced training in writing. We are at home with the humanities: philosophy, drama, the arts, aesthetics. We connect easily to both the teaching of literature and to literary exegesis. Ideas about literacy come easily to us. We need to be aware of work being done in the field outside our focus in writing, literature, and language. Connections need to be made between us and other members of our cultural tapestry. Every once in a while someone tells me about the name of a book, an organization, or a journal that I think our member-ship might be interested in. It gives me pause. I have been poking around in this area and have come up with a starter list of like-minded organizations and publishers. The Association for Humanistic Psychology, the California Institute for Integral Studies, the Esalen Institute, the Global Alliance for Transforming Education, the International Society for Traumatic Studies, the Creative Education Foundation, the Collaborative for the Advancement of Social and Emotional Learning at Yale, the Institute of Noetic Sciences, and the Naropa Institute pursue advanced ways to read, to learn, to think, to share ideas and approaches to learning in ways that lie beyond the traditional academic framework. Several periodicals and presses specialize in publishing work of this nature: Holistic Education Review (and Press), The Journal of Consciousness Studies, The Brain/Mind Bulletin, and Zephyr Press. Others specialize in helping people network: Great Ideas in Education, Association of Supervision and Curriculum Development's Network for Research on Affective Factors in Education (and quarterly newsletter), the Resource Center for Redesigning Education, The News-letter for the Association for Rhetoric, Writing, and The Transcendent, out of Washburn University. I encourage readers to become acquainted with these organizations, interest groups, and publishers. Some of the materials that have emerged from them are sufficiently noteworthy to suggest book reviews, annotated bibliographies, and critical essays. Some of the conferences that these organizations hold are sufficiently similar to our workshops to invite some form of cross-fertilization. An interesting side note concerning our organization: One contributor asked me, how political are we? I answered, everything we are and everything we do is political, as political as we are human. Poet William Stafford once said that anyone who breathes is in the rhythm business. Well, anyone who believes is in the political business. The very fact of life is a unending impulse to stay alive, to thrive. It is an assertion. Moreover, every act bears a stamp of interpretation, subjectivity, slant; things we reject; things we perceive in certain ways; things we would like to see done a certain way. Nonetheless, the AEPL tries to be as inclusive as possible, inviting ideas of all shapes and sizes. But material should in some way embody alternative approaches to learning language, and teaching: Consider the following issues as the bases for contributions: How a subject uniquely stimulates language use or teaching; what its potential and problems are from a critical perspective; how it is linked to issues of knowledge, self, and culture; what its connections are to contemporary disciplinary debates within contemporary studies and/or studies of language use and teaching; what its relationship is to ongoing AEPL themes that are emerging in workshops, the summer conference, and the journal. Let me mention some staff changes: I would like to welcome Hildy Miller as Assistant Editor and to thank Mary Deming for pushing the journal from behind as it got going. I welcome Ann Mullin as Book Review Editor, and Sharon Gibson-Groshon and Bruce Ardinger as members of the Editorial Advisory Board. With this issue Martha Goff Stoner officially becomes an editorial assistant. She proofreads copy at the very last stages of production and helps compile our style sheet. Our theme for the next volume is Resistance and Rewards Beyond the Cognitive Domain. By this I mean stories of personal discomfort in, student resistance to, administrative or community hesitance about or interference with the borderland. What issues develop when we teach and learn language in territories beyond the cognitive. By the same token, I also mean stories of personal discovery or renewal, student growth, administrative and community cooperation, so that advances in language education are realized in enabling and constructive ways—how we relate to our administration, colleagues, countermovements, and students.